Vesna Pavlovic : Stagecraft - Curley, John J.; Amirkhani, Jordan; Dimitrijević, Branislav; Vesić, Jelena, 1974-; Pavlović, Vesna, 1987-; Dimitrijević, Branislav (Book collections on Project MUSE., 2021)
"Features four extensive bodies of the photographer's work, spanning from the early 2000s to today-photographs of the Yugoslav socialist modernist hotel spaces from her series Hotels; photographs of the ceremonial space of the Yugoslav Presidential Palace in Belgrade from the series Collection/Kolekcija, and the recent Fabrics of Socialism and Sites of Memory series exploring the archives of the Museum of Yugoslav History. Includes critical essays that contextualize and expound on Pavlović's unique treatment of the photographic medium, in which a photographic moment is expanded to include the conditions of image making, production, documentation, and representation"--